Relationship between Chronic Periodontitis and Erectile Dysfunction: A Narrative Review. (13th March 2016) - Shariff, Jaffer A.; Ingleshwar, Aparna; Lee, Kevin C.; Zavras, Athanasios I.
Abstract : Objective . To conduct a descriptive literature review on research studies investigating the association between chronic periodontitis (CP) and erectile dysfunction (ED). Methods . Cohort studies, case-control studies, cross-sectional studies, randomized control trials, and animal studies up to July 2015 that studied the relationship between CP and ED were reviewed and reported. Data sources included PubMed, EMBASE, Cochrane Library, and Clinicaltrials.gov. The themes "periodontal disease" and "erectile dysfunction" and the role of periodontal therapy were identified and discussed throughout the narrative review. Results . After reviewing the literature, it was found that an association between CP and vasculogenic ED likely exists. Inflammation resulting from CP promotes endothelial dysfunction by increasing the systemic levels of inflammatory cytokines, such as tumor necrosis factor-alpha (TNF- α ). Periodontal therapy attempts to decrease the release of TNF- α and could act to restore endothelial function, particularly in the penile vasculature. Conclusion . Although the literature reported a positive association between CP and ED, the studies were few and possess several methodological limitations. Large-scale cohort studies and confounder analysis are recommended. Dentists and physicians should collaborate to manage patients with either CP or ED because of their potential association not only with each other but also with other serious systemic comorbidities.